Rheological behaviors of glass bead- and wollastonite-filled polypropylene composites modified with thermoplastic elastomers - (:unkn) unknown (WILEY, 2012)
Steady- and oscillatory-shear rheological behaviors of polypropylene/glass bead (PP/GB) and PP/wollastonite (PP/W) melts modified with thermoplastic elastomers, poly(styrene-b-ethylene-co-butylene-b-styrene) copolymer (SEBS) and the corresponding block copolymer grafted with maleic anhydride (SEBS-g-MA), were examined by means of a parallel-plate rheometer. With adding the elastomers (SEBS and SEBS-g-MA) and fillers (spherical GB and acicular W) to PP, viscosity especially at low shear rates and shear-thinning flow behavior at high shear rates were pronounced as evidenced quantitatively by CarreauYasuda (CY) parameters, but CoxMerz analogy became weakened. Besides, melt-elasticity in terminal region and relaxation time (tc) in crossing point increased, indicating an enhancement in quasi-solid behavior of molten PP. Comparing with the elastomers, rheological behaviors of molten PP were more influenced with adding the rigid fillers, especially with W due to distinct acicular shape of W particles. SEBS-g-MA elastomer more affected rheological behaviors of the ternary composites than SEBS elastomer, implying that SEBS elastomer and the filler particles behaved individually (i.e., development of separate microstructure) in (PP/GB)/SEBS and (PP/W)/SEBS ternary composites, but core-shell microstructure developed with strong interfacial adhesion by adding SEBS-g-MA elastomer, and the filler particles encapsulated with the thick SEBS-g-MA elastomer interlayer (i.e., core-shell particles) acted like neither big elastomer particles nor like individual rigid particles in melt-state. Moreover, effects of SEBS-g-MA elastomer reached a maximum on rheological behaviors of (PP/W)/SEBS-g-MA ternary composite, indicating a synergy between core-shell microstructure and acicular W particles. Correlations between oscillatory-shear flow properties and microstructures of the blends and composites were evaluated using ColeCole (CC), HanChuang (HC), and van GurpPalmen (vGP) plots. COMPOS., 2012. (C) 2012 Society of Plastics
Keywords: MECHANICAL-PROPERTIES; BLOCK-COPOLYMER; GRAFTED POLYPROPYLENE; TERNARY COMPOSITES; THERMAL-BEHAVIOR; PHASE-STRUCTURE; POLYMER BLENDS; MELT RHEOLOGY; INTERFACIAL INTERACTION; LINEAR VISCOELASTICITY